Միգրացիան ՀՀ սոցիալական անվտանգության համակարգում - Գրիգորյան, Նարեկ (YSU Journal of International Affairs, 2017)
In the contemporary situation of market economy, the modernity of monitoring of Armenia’s migration policy is due to the direct influence of migration processes on public life and infrastructures. The comparative studies of the negative consequences of migration allow assessment of efficient management trends. In this regard, the development and actualization of efficient migration policy are vital for Armenian society.
Keywords: social security, migration policy, migration settings, migration processes, human capital, armed forces of RA